A rare homozygous variant of MC2R gene identified in a Chinese family with familial glucocorticoid deficiency type 1: A case report - Liu, ShuPing; Zeng, Ting; Luo, Cheng; Peng, DanXia; Xu, Xuan; Liu, Qin; Wu, Qiong; Lu, Qin; Huang, FuRong (Frontiers in Endocrinology, 2023)
Background Melanocortin-2 receptor (MC2R), a member of the G protein-coupled receptor family, is selectively activated by adrenocorticotropic hormone (ACTH). variants in MC2R are associated with family glucocorticoid deficiency 1 (FGD1). Case presentation We first reported a Chinese family with two affected siblings with a homozygotic variant of c.712C>T/p.H238Y in MC2R, presenting with skin hyperpigmentation, hyperbilirubinemia, and tall stature. These individuals showed novel clinical features, including congenital heart defects, not been found in other FGD1 patients. Conclusions We reported a Chinese family with affected siblings having a homozygotic variant of c.712C>T/p.H238Y in MC2R.Our report may expand the genetic and clinical spectrum of FGD1.